Analysis of Factors Influencing the Utilization of the Non-Communicable Diseases Community Health Post (Posbindu) in the South Purwokerto Community Health Center, Banyumas Regency - Nadia Nisrina Razan; Devi Octaviana; Novita Endang Fitriyani; Rosita Dwi Jayanti (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2025)
Background: Non-communicable diseases (NCDs) are the leading cause of global death. The Non-Communicable Diseases Community Health Post (Posbindu PTM) aims to prevent and control NCDs, but utilization at the South Purwokerto Community Health Center remains low. The average attendance rate at each Posbindu was only 2.6 %, far below the 100% target. This study aims to analyze the factors influencing the utilization of Posbindu PTM in the region. Methods: This study analyzes the influence of variables such as gender, education level, employment status, income, knowledge, individual perception, availability of facilities, access to health services, access to information, cadre support, and family support on the utilization of Posbindu PTM in the South Purwokerto Community Health Center area. The research design used is cross-sectional , the population is the productive age community with sampling using proportional random sampling technique of 110 people. Data collection through observation and questionnaire interviews. Research data analysis consists of univariate analysis, bivariate analysis, and multivariate analysis. Results: The utilization of Posbindu PTM in the Purwokerto Selatan Community Health Center Working Area was significantly influenced by access to information (p = 0.021; OR = 5.000; CI 95% = 1.268 – 19.714). Conclusions: Access to information is a significant factor influencing the utilization of Posbindu PTM in the South Purwokerto Community Health Center working area. Therefore, the dissemination of information regarding Posbindu PTM should be expanded through routine community activities and by strengthening the role of health cadres as key implementers. Enhancing these efforts will enable the South Purwokerto community to gain a better understanding of Posbindu and recognize the importance of preventing non-communicable diseases through early detection at Posbindu PTM.